A plataforma Sucupira sob a interpreta????o dos gestores da P??s-Gradua????o em Educa????o - Pimentel, Bruno de Mac??do Cavalcanti Borges (2017)
The evaluation of the stricto sensu graduation was consolidated as an instrument of great importance for the National Graduate System (SNPG) and for the promotion of scientific research and technological development in Brazil. This research addresses the issue of the stricto sensu graduate course evaluation in Brazil according to the interpretation of the managers involved in the evaluation process of the Coordination of Improvement of Higher Education Personnel (Capes). The objective was to investigate the interpretation of the coordinators of graduate programs in education regarding the use of the Sucupira Platform for the programs evaluation during the quadrennium 2013-2016. The research has a qualitative nature, although it is based on the analysis of quantitative data. In relation to the theoretical basis, the research was developed based on the Policy Cycle Approach, developed by Stephen Ball, Richard Bowe and Anne Gold (BALL; BOWE; GOLD, 1992; BALL, 1994). This method is an important theoretical analytical tool for the understanding, study, evaluation and analysis of educational policies. Three techniques were used to investigate the object under study: the semi-structured interview carried out in four programs in the area of education in the Center-West region; The mixed format questionnaire applied electronically to all coordinators of the one hundred and seventy four education programs currently operating in the country; And documentary analysis. The questionnaires were sent and the data processed through the computer program "SurveyMonkey". The research data were analyzed based on content analysis according to Laurence Bardin (2011). The data indicate that the coordinators of the education programs identify the integration of the Platform with the other instruments, but ask for improvement in this interaction. The coordinators recognize the Platform as the main instrument for the evaluation of graduate studies and its importance for the improvement of the SNPG. They interpret the filling in the Platform data according to the realities and the peculiarities of its programs and seek to adapt to the requirements of Capes for the evaluation. They report difficulties in filling in the programs data in the Platform, since it is an eminently manual, detailed, exhaustive activity that still has operational failures on the system. However, they recognize the substantial improvement in the process of sending the Data Collection. In general, the filling in the Platform data is done by the secretaries of the programs, supervised by the coordinators. The questionnaire data and the interviewed managers' talk about the Sucupira Platform's contributions and the objectives reached demonstrate the success of the system. However, they criticize some specific points of the Platform, such as the loss of registered data. They also criticize the Capes evaluation system, especially in relation to the criteria used in the periodic evaluations of the programs and the Qualis system classification of the teachers and students intellectual production evaluation. The research suggests improvements in the management of programs data in the Platform by the coordinators and the improvement of the evaluation process of the graduate programs by Capes.